Language Diversity of Hotel Signage: Insights from Surabaya - Susanto, Fajar; Tafuzi, Novta Ittaqy (Universitas Muhammadiyah Tangerang, 2025)
This study explores the language diversity in hotel signage in Surabaya. The hotel signage can be met at many places in the areas of hotels and provides guidelines for their guests during staying at the hotel. The aim of this study is to explore language diversity in hotel signage in the hotels. To describe the use of language diversity of hotel signage, this study was designed in the frame of the qualitative case study in which the data were collected through on-site observation and taking the photos of hotel signage in the areas of hotels. The study found five types of signage that are used at the hotels, such as identification signage, directional signage, informational signage, orientation signage, and regulatory signage. This study provides insight into the importance of language diversity in the hotel industry and the need for the hotels to give information through diversities of language signage to their guests. This study indicates the language diversities of hotel signage which have multiple register use.